The stabilizing effect of water-drought rotation on soil microbial communities: potential for resisting obstacles in continuous cropping - Chen, Li; Fan, Caiyin; Su, Liang; Zhang, Deyong; Zhu, Chunhui; Feng, Weiping; Zhou, Jindong; Cheng, Ju’e; Du, Xiaohua; Sun, Shu’e (Frontiers in Agronomy, 2026)
IntroductionContinuous soil monocropping typically disrupts microecological equilibrium, leading to reduced crop yield and quality degradation, whereas crop rotation often mitigates these issues. However, understanding of the microbial mechanism behind this rotation practice is still limited.MethodsA three-year field experiment was conducted comparing tobacco continuous monocropping and tobacco-rice rotation. The bacterial community structure, assembly processes, and functional profiles were analyzed within three tobacco growing periods.ResultsWhile most soil physicochemical parameters, such as pH, total phosphorus, and available phosphorus, were not significantly different between the two systems, tobacco monoculture specifically resulted in elevated contents of total nitrogen and alkali-hydrolyzable nitrogen compared to tobacco-rice rotation systems. Although α-diversity also showed no significant differences between systems, bacterial community composition diverged significantly, with Proteobacteria, Acidobacteria, and Actinobacteria dominating. Deterministic processes governed community assembly, with βMNTD and βNTI exhibiting significant correlations with soil available nitrogen, phosphorus, potassium, and pH exclusively in the rotation system-contrasting sharply with the absence of such correlations in monoculture. Tobacco-rice rotation exhibited more complex co-occurrence networks anchored by 22 topological connector taxa than tobacco monocropping. Functionally, the rotation significantly suppressed nitrifying bacteria abundance, whereas monocropping enriched dark sulfide-oxidizing bacteria. Notably, despite the absence of significant overall differences in pathogen abundance between the two cropping systems, a high variation was observed of plant pathogen abundance in the vigorous growth stage of tobacco monocropping, which indicates that certain locations possess a considerably elevated susceptibility to potential disease epidemics.DiscussionCompared to continuous monocropping, tobacco-rice rotation caused minimal shifts in soil α-diversity and physicochemical properties. However, our three years field study reveals that it profoundly restructured the composition and interaction networks of the soil bacterial community. This highlights the divergent impacts of cropping systems on the soil microbiome and indicates that the benefit of rotation may stem primarily from its ability to rewire microbial interactions, thereby alleviating continuous cropping obstacles.